2007
DOI: 10.1111/j.1745-7262.2007.00308.x
|View full text |Cite
|
Sign up to set email alerts
|

Orchestration of occludins, claudins, catenins and cadherins as players involved in maintenance of the blood-epididymal barrier in animals and humans

Abstract: Although spermatozoa are formed during spermatogenesis in the testis, testicular spermatozoa are immature and cannot swim or fertilize. These critical spermatozoal functions are acquired in the epididymis where a specific luminal environment is created by the blood-epididymal barrier; proteins secreted by epididymal principal cells bind to maturing spermatozoa and regulate the maturational process of the spermatozoa. In the epididymis, epithelial cell-cell interactions are mediated by adhering junctions, neces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 67 publications
1
52
0
1
Order By: Relevance
“…In all species examined, we used tissue samples from various portions of the excurrent ducts, which are known to contain typical simple or columnar epithelia, as controls of the methods applied and to determine the specificity of the antibodies used in immunocytochemistry of the seminiferous tubules (for references, see, e.g., Dym 1974, 1976, 1977; Kasper and Stosiek 1989; Cyr et al 1995, 2007; Piomboni 1997; Pelletier 2001; DeBellefeuille et al 2003). Frequently, it was possible for us to study testicular tissue containing seminiferous tubules in parallel with preparations of excurrent duct tissues, including the epididymis, from the same animal.…”
Section: Resultsmentioning
confidence: 99%
“…In all species examined, we used tissue samples from various portions of the excurrent ducts, which are known to contain typical simple or columnar epithelia, as controls of the methods applied and to determine the specificity of the antibodies used in immunocytochemistry of the seminiferous tubules (for references, see, e.g., Dym 1974, 1976, 1977; Kasper and Stosiek 1989; Cyr et al 1995, 2007; Piomboni 1997; Pelletier 2001; DeBellefeuille et al 2003). Frequently, it was possible for us to study testicular tissue containing seminiferous tubules in parallel with preparations of excurrent duct tissues, including the epididymis, from the same animal.…”
Section: Resultsmentioning
confidence: 99%
“…Among mRNA targets that were negatively correlated with the levels of their corresponding miRNAs, Cldn10 was particularly interesting with regards to epididymal function and fertility [1], [59]. Cldn10 has been shown to be involved in the paracellular transport of cations across epithelial tight junctions [60], [61] and is expressed in tight junctions of the human epididymis [1], [59].…”
Section: Discussionmentioning
confidence: 99%
“…There is surprisingly limited information about the hormones and intracellular signaling pathways implicated in the formation and maintenance of the blood-epididymis barrier [23]. Because the IHCE1 cells do not form functional tight junctions, we compared gene expression profiles with human epididymal principal cells (FHCE1) that were derived from a fertile patient and were shown to form functional tight junctions, in order to identify regulatory pathways that may be implicated in the regulation of epididymal tight junctions [37].…”
Section: Discussionmentioning
confidence: 99%
“…Tight junctions are composed of integral proteins such as occludin (OCLN), tricellulin, and a larger family of proteins, the claudins (CLDNs) [22,23]. It has previously been reported that the rat and human epididymis contain a large number of CLDNs [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%